ANALYSIS OF SCHOOL READINESS IN CHILDREN AGED 5-6 YEARS AT PAUD UMMUL HABIBAH IN KLAMBIR V KEBON VILLAGE, DELI SERDANG REGENCY - Munisa, Munisa; Nofianti, Rita; Andini, Naya Rama (Proceeding International Seminar of Islamic Studies, 2024)
The readiness of children to begin formal schooling is a critical factor in their educational journey, impacting their ability to adapt and succeed in a structured learning environment. This study aims to analyze the school readiness of children aged 5-6 years at PAUD Ummul Habibah, located in Klambir V Kebon Village, Deli Serdang Regency. Utilizing a descriptive qualitative approach, the research investigates various dimensions of school readiness, including cognitive, social-emotional, physical, and language development. Data were collected through observations, structured interviews with educators and parents, and assessments of children's developmental milestones. The findings indicate that while a majority of the children demonstrate adequate cognitive and language skills, there are notable variances in social-emotional readiness and physical development. Factors influencing these variances include family background, early childhood education experiences, and parental involvement. The study underscores the importance of comprehensive early childhood programs that address all aspects of school readiness and suggests targeted interventions to support areas where children are less prepared. The results provide valuable insights for educators and policymakers in enhancing early childhood education strategies to ensure all children are equipped for the transition to formal schooling.